Bargaining, mergers, and technology choice in bilaterally oligopolistic industries - Roman Inderst; Christian Wey (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This paper provides a conceptual framework of multilateral bargaining in a bilaterally oligopolistic industry to analyze the motivations for horizontal mergers, technology choice, and their welfare implications. We first analyze the implication of market structure for the distribution of industry profits. We find that retailer mergers are more likely (less likely) if suppliers have increasing (decreasing) unit costs, while supplier mergers are more likely (less likely) if goods are substitutes (complements). In a second step we explore how market structure affects suppliers' technology choice, which reflects a trade-off between inframarginal and marginal production costs. We find that suppliers focus more on marginal cost reduction if (i) retailers are integrated and (ii) suppliers are non-integrated. In a final step we consider the whole picture where both market structure and (subsequent) technology choice are endogenous. Analyzing the equilibrium market structure, we find cases where retailers become integrated to induce suppliers to choose a more efficient technology, even though integration weakens their bargaining position. In this case the merger benefits all parties, i.e., suppliers, retailers, and even consumers. However, we also show that the equilibrium market structure does often not maximize welfare. – – Der Aufsatz analysiert zuerst, wie die Marktstruktur die Verteilung der Industrieprofite zwischen den Firmen bestimmt, woraus sich eindeutige Bedingungen für profitable Zusammenschlüsse ableiten lassen: Firmen des Einzelhandels stellen sich durch einen Zusammenschluß besser (schlechter), wenn die Herstellerfirmen mit steigenden (fallenden) Durchschnittskosten produzieren. Herstellerfirmen profitieren durch einen Zusammenschluß, wenn sie substituierbare Güter anbieten, während sie sich durch eine Fusion schlechter stellen, wenn sie komplementäre Güter absetzen. Der nächste Schritt der Untersuchung erkundet die Wirkungen der Marktstruktur auf die Technologiewahlanreize der Hersteller, wobei die Adaption einer neuen Technologie einerseits mit niedrigeren marginalen Kosten und andererseits mit höheren inframarginalen (oder Fix-) Kosten einhergeht. Es zeigt sich, daß Herstellerfirmen höhere Anreize zur Senkung ihrer marginalen Kosten haben, wenn (i) der Einzelhandel vollständig monopolisiert ist und (ii) die Herstellerfirmen nicht integriert sind.
Keywords: D40; L10; L40; 330; Bilateral Oligopoly; Antitrust; Bargaining Power; Merger; Retailing; Technology Choice